MIR205HG/LEADR Long Noncoding RNA Binds to Primed Proximal Regulatory Regions in Prostate Basal Cells Through a Triplex- and Alu-Mediated Mechanism - Bezzecchi, Eugenia; Pagani, Giulia; Forte, Barbara; Percio, Stefano; Zaffaroni, Nadia; Dolfini, Diletta; Gandellini, Paolo (Frontiers in Cell and Developmental Biology, 2022)
Aside serving as host gene for miR-205, MIR205HG transcribes for a chromatin-associated long noncoding RNA (lncRNA) able to restrain the differentiation of prostate basal cells, thus being reannotated as LEADR (Long Epithelial Alu-interacting Differentiation-related RNA). We previously showed the presence of Alu sequences in the promoters of genes modulated upon MIR205HG/LEADR manipulation. Notably, an Alu element also spans the first and second exons of MIR205HG/LEADR, suggesting its possible involvement in target selection/binding. Here, we performed ChIRP-seq to map MIR205HG/LEADR chromatin occupancy at genome-wide level in prostate basal cells. Our results confirmed preferential binding to regions proximal to gene transcription start site (TSS). Moreover, enrichment of triplex-forming sequences was found upstream of MIR205HG/LEADR-bound genes, peaking at −1,500/−500 bp from TSS. Triplexes formed with one or two putative DNA binding sites within MIR205HG/LEADR sequence, located just upstream of the Alu element. Notably, triplex-forming regions of bound genes were themselves enriched in Alu elements. These data suggest, from one side, that triplex formation may be the prevalent mechanism by which MIR205HG/LEADR selects and physically interacts with target DNA, from the other that direct or protein-mediated Alu (RNA)/Alu (DNA) interaction may represent a further functional requirement. We also found that triplex-forming regions were enriched in specific histone modifications, including H3K4me1 in the absence of H3K27ac, H3K4me3 and H3K27me3, indicating that in prostate basal cells MIR205HG/LEADR may preferentially bind to primed proximal regulatory elements. This may underscore the need for basal cells to keep MIR205HG/LEADR target genes repressed but, at the same time, responsive to differentiation cues.